[Pharmacoeconomic Comparison Between Dupilumab and Tralokinumab for the Treatment of Atopic Dermatitis in Italy: A Cost-per-Responder Analysis] - Paolo Gisondi; Andrea Chiricozzi; Marcello Pani; Massimiliano Povero; Luca Castello; Maria Paola Pedone; Kerry Noonan; Zhixiao Wang; Roberta Di Turi (Farmeconomia: Health Economics and Therapeutic Pathways, 2025)
OBJECTIVE: A cost-per-responder model was developed to compare the pharmacoeconomic value of dupilumab and tralokinumab, in combination with topical corticosteroids (TCS), for treating atopic dermatitis (AD) in Italy. METHODS: An indirect treatment comparison (ITC) was conducted using placebo arms from the LIBERTY AD CAFÈ, LIBERTY AD CHRONOS, and ECZTRA studies as a common comparator to assess the efficacy of dupilumab versus tralokinumab in adult AD severe patients with inadequate responses to cyclosporine. Response was evaluated at 16 weeks using different clinical outcomes: proportion of patients achieving Eczema Area and Severity Index (EASI) improvement by more than 50/75/90%, ≥4-point improvement in Itch Numeric Rating Scale (I-NRS 4), and Investigator’s Global Assessment of clear/almost clear skin score (IGA 0/1). Number Needed to Treat (NNT) associated with each efficacy outcome was calculated for dupilumab and tralokinumab (versus best supportive care [BSC]) and multiplied by the 16-week cost of treatment in order to estimate the cost per additional responder over this period. Since ex-factory prices of dupilumab and tralokinumab may not reflect the actual transfer prices charged to healthcare facilities, a scenario analysis was conducted assuming hypothetical additional discounts between 0 and 60%. Finally, an additional scenario analysis was implemented by estimating the response rate at 52 weeks. RESULTS: Dupilumab was more effective than tralokinumab across all assessed efficacy indicators. In the base case analysis, using EASI 50 as the efficacy indicator, the NNT for dupilumab was 3 patients compared to 8 patients for tralokinumab. The 16-week cost per responder was €15,595 for dupilumab and €41,587 for tralokinumab, resulting in a saving of €25,992 per patient treated effectively. In all scenario analyses, considering other efficacy indicators, dupilumab was found to be more cost-effective than tralokinumab, with savings ranging from €26,000 to €47,000 per responder, depending on the efficacy indicator considered. Dupilumab confirmed its economic advantage for all possible price reduction combinations with savings ranging from €1,000 to €56,000. The same results were also found in the 52-week endpoint analysis. Finally, assuming a fixed budget of €38 million, 1,725 additional patients can be treated effectively every year with dupilumab instead of tralokinumab. CONCLUSIONS: The findings of this study demonstrate that dupilumab provides significantly greater efficacy improvements and economic benefits compared to tralokinumab in AD patients. These results underscore the pharmacoeconomic advantages of dupilumab for managing severe AD in Italy, emphasizing its potential as a preferred treatment option for healthcare decision-makers.